Utilization of Rice Washing Water as Additional Nutrition and Environmentally Friendly Liquid Organic Fertilizer (POC) for Chili Plants in Green House Activities in Balongsari Village - Achmad Muchammad; Kamila Zain Putri Alysia (Future Tecno-Science Publisher, 2025)
This Community Service Program (KKN) aims to explore and implement the use of rice washing water as an additional nutrient and environmentally friendly liquid organic fertilizer (POC) for chili plants in a greenhouse located in Balongsari Village, Gedeg District, Mojokerto Regency. Rice washing water, which is often discarded, is rich in essential nutrients such as B vitamins and minerals that can support plant growth. Through this approach, the program seeks to reduce domestic waste and promote more sustainable and environmentally friendly agricultural practices. The expected outcomes of this program are increased knowledge and skills of local farmers in using environmentally friendly organic materials, as well as demonstrating that rice washing water can be effectively used as a nutrient supplement and liquid organic fertilizer. The program also aims to raise awareness of the importance of sustainable agricultural practices and improved waste management, with positive impacts on the environment and agricultural yields.